Pragmatic competence of Indonesian EFL learners - Retnowaty, Retnowaty ((JELE) Journal Of English Language and Education, 2017)
Pragmatic competence is the skill to communicate in foreign language intended meaning. The objective of the study is to describe pragmatic competence of Indonesian EFL learners. This study was using descriptive qualitative approach. The participants were EFL learners, especially students in the first semester which take English course in Balikpapan University majoring mathematics and Health and Safety Environment. Furthermore, pragmatic test in the form of multiple choice DCT was used to assess learners’ pragmatic competence. It was applying and/or adapting some of the items devised by Rover (2005: 122-129 and Hudson, Detmer and Brown (1995: 107-130) in Viljamaa (2012). Based on the analysis of the test, most learners have quite low pragmatic competence in implicature and speech act part. Although cultural background is usually a quite problem for us, it can be handled by a good cooperation and good awareness of pragmatic aspects between the speaker and the hearer. Therefore, we should increase our pragmatic competence in everyday life with many kinds of English activities because English is still a foreign language in Indonesia.